P023 Impact of Juvenile Idiopathic Arthritis on schooling and family life. (11th November 2021) - Miri, Sirine; Triki, Wafa; Maatallah, Kaouther; Ferjani, Hanene; Ben Nessib, Dorra; Kaffel, Dhia; Hamdi, Wafa
Abstract: Background: Juvenile Idiopathic Arthritis (JIA) and its related symptoms have been associated with interference in the daily life of children and adolescents with JIA including their friendships, their school attendance and sometimes their family life. The aim of the study was to describe the impact of JIA on schooling, social and family life from the point of view of children. Methods: We interviewed 23 children and adolescents, diagnosed with JIA according to the classification criteria of the International League of Associations for Rheumatology (ILAR). Results: The mean age of our group was 16 years, with a sex ratio of 3. Eight percent of the children were in elementary school, 21.7% in high school and 8.7% in university. Eighty-seven per cent reported school absenteeism due to JIA (pain, being hospitalized, ) with a mean of 8 missed school days. Forty-three per cent failed in their schooling at some point. Thirty percent thought it was related to the consequences of their disease. Only 47.8% found the school staff to be helpful and supportive. Seventy eight percent felt understood and supported by their family in dealing with the different aspects of JIA. Twenty-six per cent felt more spoiled than their other siblings, creating tension sometimes. Fifty two percent felt different and not accepted by their peers because of the JIA. Conclusions: Children with JIA are already suffering from the physical aspect of their disease. Initiating an open discussion with them might reduce the burden these children are carrying often in silence, and improve long-term outcomes in terms of schooling, social and, family life.